2018
DOI: 10.1038/nprot.2018.024
|View full text |Cite
|
Sign up to set email alerts
|

Global site-specific analysis of glycoprotein N-glycan processing

Abstract: N-glycans contribute to the folding, stability and functions of the proteins they decorate. They are produced by transfer of the glycan precursor to the sequon Asn-X-Thr/Ser, followed by enzymatic trimming to a high-mannose-type core and sequential addition of monosaccharides to generate complex-type and hybrid glycans. This process, mediated by the concerted action of multiple enzymes, produces a mixture of related glycoforms at each glycosite, making analysis of glycosylation difficult. To address this analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 78 publications
(132 reference statements)
2
64
0
Order By: Relevance
“…interference of the biosynthetic processing pathway, our observations were unexpected since HA is substantially less glycosylated than the surface glycoproteins of numerous other viruses. With up to thirty N-linked glycans per monomer, both HIV gp120 and MERS CoV S-2P are well-characterized examples that comprise numerous oligomannose sites arising due to close packing of their many structurally proximal glycosites (Cao et al, 2017(Cao et al, , 2018. By contrast, HA glycans are far fewer and appear sparsely arranged (Figure 4), suggesting that in this case, presence of oligomannose glycans is not due to steric restrictions imposed by neighboring glycan chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…interference of the biosynthetic processing pathway, our observations were unexpected since HA is substantially less glycosylated than the surface glycoproteins of numerous other viruses. With up to thirty N-linked glycans per monomer, both HIV gp120 and MERS CoV S-2P are well-characterized examples that comprise numerous oligomannose sites arising due to close packing of their many structurally proximal glycosites (Cao et al, 2017(Cao et al, , 2018. By contrast, HA glycans are far fewer and appear sparsely arranged (Figure 4), suggesting that in this case, presence of oligomannose glycans is not due to steric restrictions imposed by neighboring glycan chains.…”
Section: Discussionmentioning
confidence: 99%
“…This proteomics-based method for site-specific analysis of N-linked glycan processing uses endoglycosidases to introduce mass signatures that contain either no glycan, minimally processed high-mannose or hybrid-type, or more extensively processed complex-type N-glycans. This allows a semi-quantitative assessment of the proportion of each glycoform present at each glycosite (Cao et al, 2017(Cao et al, , 2018.…”
Section: Influenza Has From Diverse Subtypes Exhibit Substantial Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…5c). To interrogate the nature of the glycan chain present on SPRING we used Endoglycosidase-H (Endo-H), which removes glycans from ER-and cis/medial Golgi-resident proteins, before they acquire complex modifications 31 . We observed that unlike LDLR, SPRING glycosylation remained Endo-H-sensitive (Supplementary Fig.…”
Section: Spring Is a Glycosylated Golgi-resident Membrane Proteinmentioning
confidence: 99%
“…introduce unique mass signatures for (potential) sites of glycosylation that carry no glycan, high-mannose/hybrid type glycans, and complex glycans [75 ]. These strategies have arisen from the need for a HIV-1 vaccine that utilizes HIV-1 Env, which contains 75-90 N-glycans [76].…”
Section: Site-specific Glycan Profilesmentioning
confidence: 99%